Muscular and neuronal control of voice production – forgotten findings, current concepts, and new developments - Tracicaru, Rares; Bräuer, Lars; Döllinger, Michael; Hînganu, Delia; Paulsen, Friedrich; Hînganu, Marius Valeriu (Annals of Anatomy-Anatomischer Anzeiger, 2024)
Voice production has been an area of interest in science since ancient times, and although advancing research has improved our understanding of the anatomy and function of the larynx, there is still little general consensus on these two topics. This review aims to outline the main developments in this field and highlight the areas where further research is needed. The most important hypotheses are presented and discussed highlighting the four main lines of research in the anatomy of the human larynx and their most important findings: (1) the arrangement of the muscle fibers of the thyroarytenoid muscle is not parallel to the vocal folds in the internal part (vocalis muscle), leading to altered properties during contraction; (2) the histological structure of the human vocal cords differs from other striated muscles; (3) there is a specialized type of heavy myosin chains in the larynx; and (4) the neuromuscular system of the larynx has specific structures that form the basis of an intrinsic laryngeal nervous system. These approaches are discussed in the context of current physiological models of vocal fold vibration, and new avenues of investigation are proposed.
CRIS-Team Scopus Importer:2024-05-31
Keywords: Intramuscular ganglia; Larynx; Muscle spindle; Myosin heavy chain; Neuromuscular junctions; Vocal fold oscillation; Voice